Inventarisasi Tumbuhan Air Di Kawasan Wisata Air Terjun Bidadari Desa Kawinda To’i Kecamatan Tambora Kabupaten Bima - Mas’anah; Fitriani; Nehru; Hartati; Azmin, Nikman (JUSTER : Jurnal Sains dan Terapan, 2023)
Indonesia is a country that have biodiversity. One type of plant diversity that is commonly found in Indonesia is aquatic plants. Aquatic plants are plants that part or all of their life cycle are in water, have a role as primary producers in waters which are a source of food for primary consumers or biophages. This study aims to determine various types of aquatic plants in the Tambora Angel Waterfall area, Bima district, the research was carried out in May 2023. The research method used was the cruising method, namely with a limit of 100 meters from the three stations. The research results found 5 types of aquatic plants, namely Cheilocoestue speciosus , Chromolaena odorata, Teminalia catappa, Boeharvia erecta, and Boehmeria grandis.